Contingency Theory and Its Implications to Corporate Financial Planning and Organization Structure - Anwar, Mokhamad (Universitas Brawijaya, Indonesia, 2015)
The development of the organization theory has existed for such long periodsespecially in terms of management theory. The driving force behind the evolution of management theory is that its efforts to look for better ways in managing organizational resources.Contingency theory which is a part of the organizational environment theories has broughtmany implications in management's decision at any organization. Especially in finance,contingency theory has been employed in some financial decisions including the decision ofcorporate financial planning as a part of the most important considerations, and thoseactions would certainly have implications to the corporate organizational structure. Thecontingency theory has been implemented by financial managers in decision making especiallyin strategic long-term and short-term financial planning regarding many assumptionsthat underlying the decision. In practice, financial managers can implement the contingencytheory by using Scenario Planning. The advantages of the contingency theory are thatthe theory has enriched the management theories by addressing the environment as one ofthe keys for managerial decision making. The theory has also helped management of organizationsin improving the quality of decision making by addressing the contingent variables.The limitation of the contingency theory is that the contingent factors are still in debatesuntil nowadays so that we cannot determine the precise numbers of contingent factors.